Processos discursivos de objetivação e subjetivação de mulheres vítimas de estupro - Lemes, Fabiane (2024)
This PhD Thesis aims to analyze discursive processes of objectification and subjectivation of women who are victims of rape. To this end, the research questions were outlined in order to understand how these women are discursively constructed and how they construct themselves from within two materialities that constitute the research corpus, namely: medical records of women who have been sexually assaulted, treated by the Hospital de Clínicas de Uberlândia in partnership with Nuavidas (Nucleus of Comprehensive Care for Victims of Sexual Assault); and accounts from women, also affected by the crime, shared by the victims and posted online. Specifically, it analyzes the institutional discursive practices inherent to the structure of the medical records we accessed, from which we scrutinize the processes of objectification, as well as the discursive practices of women who, by recounting their experiences, discursively construct rape while also subjectivizing themselves as victims of this violence. By situating ourselves within the field of Critical Applied Linguistics, a science that encourages a theoretical and methodological hybridism allowing us to expand interpretative frameworks regarding the discursive construction of rape, we weave as part of the epistemological journey we establish an investigation into the woman-man relationships throughout history, which permeate processes of objectification and subjectivation. By positioning ourselves in the area of language studies, we conduct our analysis through a descriptive-interpretative lens intrinsic to materialist Discourse Analysis, specifically drawing on theoretical contributions from Michel Foucault (1987, 1988, 1995, 1996, 2007, 2008, 2010, 2012) and Michel Pêcheux (1997, 1999). From the analysis conducted, we understand that the way language is mobilized in medical records, as well as the descriptions of events reported by the victim, can reflect a bias that minimizes and reinforces a discursive formation that blames the rape victim. Furthermore, we envision that rape is rooted in discursive practices and power relations that perpetuate sexual violence and render rape committed against women a systematically structural act. We emphasize that this research is epistemologically justified as it contributes to discursive, historical, and cultural research encompassing the theme of women and femininity as objectified and subjectified bodies in the discourse of sexual violence, and socially, by making a pressing issue more visible, whose complexity demands attention from all sectors of society.